Development and Implementation of Sustainability IoT Based Curriculum - Amr Elsaadany; Ahmed Helmi (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Dubrovnik, Croatia, 7-9 September 2017, 2017)
Sustainable development has three main pillars, economic, social, and environmental. In the strive for a sustainable world, environmental and social issues must be addressed as they affect the world economy. With the past industrial revolutions and their negative effects on our world, it is becoming essential to involve students in sustainability as engineering and technology are important elements into fixing the past negative effects on our planet. Consequently, educating engineering students on sustainable development is wide spreading in the past few years and is actually taking place worldwide in many modern faculties and universities. Aside from the United Nations mandates, it is those engineers who are to make the efforts in their respective fields to create ways to improve the sustainable world around us. There are many methods to go about teaching such a subject, some are direct and some uses indirect methods. Building upon the experience of others and the wide spectra of methods, a new curriculum is designed, based on innovations in technologies, to cover sustainability along with environmental and social implications. The curriculum relies on a mixture of learning techniques especially suitable for a developing and growing educational environment where the subject matter experts are not abundantly available. The method used in the design and implementation allows flexible usage and integration of the course by educational institutions and new universities. The results of applying the course content on a sample of 50 student is collected and analysed. The tabulated data and graphs show the strong points of the course materials as well as the areas of improvements
Keywords: I20; 330; sustainable development; teaching methodology; educational systems; learning outcomes; data analysis; ICT; IoT